2002
DOI: 10.1063/1.1476007
|View full text |Cite
|
Sign up to set email alerts
|

On the required shape corrections to the local density and generalized gradient approximations to the Kohn–Sham potentials for molecular response calculations of (hyper)polarizabilities and excitation energies

Abstract: It is well known that shape corrections have to be applied to the local-density ͑LDA͒ and generalized gradient ͑GGA͒ approximations to the Kohn-Sham exchange-correlation potential in order to obtain reliable response properties in time dependent density functional theory calculations. Here we demonstrate that it is an oversimplified view that these shape corrections concern primarily the asymptotic part of the potential, and that they affect only Rydberg type transitions. The performance is assessed of two sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 43 publications
(27 reference statements)
2
107
0
Order By: Relevance
“…The experimental determination of the latter value seems to be quite difficult in view of the complicated structure of the N 2 absorption spectrum in this energy range and the low oscillator strength of this transition, making a deconvolution into contributions of at least three different electronic states necessary. We also quote in the table the alternative assignment of the orbital transitions to the experimentally observed states, which as noted by Grün-ing et al 13 and mentioned in the Introduction, would considerably improve the agreement of the calculations with the experimental vertical excitation energies from the more recent Ref. 1.…”
Section: Vertical Excitationsmentioning
confidence: 93%
See 4 more Smart Citations
“…The experimental determination of the latter value seems to be quite difficult in view of the complicated structure of the N 2 absorption spectrum in this energy range and the low oscillator strength of this transition, making a deconvolution into contributions of at least three different electronic states necessary. We also quote in the table the alternative assignment of the orbital transitions to the experimentally observed states, which as noted by Grün-ing et al 13 and mentioned in the Introduction, would considerably improve the agreement of the calculations with the experimental vertical excitation energies from the more recent Ref. 1.…”
Section: Vertical Excitationsmentioning
confidence: 93%
“…Details of the basis can be found in Ref. 13. For ground-state structure optimization, frequency analysis, and reference energy calculations, we employed the Becke-Perdew-Wang exchange-correlation functional, dubbed BPW91; 29,30 test calculations showed that other generalized-gradient approximations to the exact exchangecorrelation functional yield very similar results.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations